2021
DOI: 10.2337/db20-1072
|View full text |Cite
|
Sign up to set email alerts
|

The Repertoire of Newly Developing Regulatory T Cells in the Type 1 Diabetes–Prone NOD Mouse Is Very Diverse

Abstract: Regulatory T lymphocytes expressing the forkhead/winged helix transcription factor Foxp3 (Treg) play a vital role in the protection of the organism from autoimmune disease and other immunopathologies. The antigen-specificity of Treg plays an important role in their in vivo activity. We therefore assessed the diversity of the T cell receptors for antigen (TCR) expressed by Treg newly developed in the thymus of autoimmune type I diabetes-prone NOD mice and compared it to the control mouse strain C57BL/6. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…However, for both populations, much fewer cells proliferated in NOD than in B6 mice. It was recently shown that whereas the diversity of the TCR repertoire expressed by newly developed Tregs is similar in B6 and NOD mice (8), in peripheral lymphoid organs, this diversity is higher in NOD than in B6 mice. This phenomenon was apparently due to reduced clonal Treg expansion in NOD mice (41), which in turn is probably caused by limited production of IL-2 in NOD as compared with B6 mice (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for both populations, much fewer cells proliferated in NOD than in B6 mice. It was recently shown that whereas the diversity of the TCR repertoire expressed by newly developed Tregs is similar in B6 and NOD mice (8), in peripheral lymphoid organs, this diversity is higher in NOD than in B6 mice. This phenomenon was apparently due to reduced clonal Treg expansion in NOD mice (41), which in turn is probably caused by limited production of IL-2 in NOD as compared with B6 mice (9).…”
Section: Discussionmentioning
confidence: 99%
“…Inherited defects in Treg-mediated immunoregulation may be involved in susceptibility to autoimmune diseases such as T1D. It was reported that the TCR repertoire expressed by Tregs developing in NOD mice was of limited diversity (7), but our recent highthroughput TCR-mRNA sequencing data challenged this conclusion (8). Polymorphisms in genes encoding IL-2 and its receptor components, which may affect in-vivo Treg function, are linked to diabetes in humans and mice (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 98%